Strategi Pengembangan Investasi Di Pelabuhan Perikanan Nusantara (PPN) Pengambengan, Bali - I Ketut Wija Negara; Dewa Ayu Angga Pebriani; Ni Putu Putri Wijayanti; Andi Mannojengi; Bagus Sudananjaya; Kadek Adi Chandra Kusuma (Fakultas Kelautan dan Perikanan Universitas Udayana, 2022)
The construction of a fishing port has been able to have an impact on growth in the economic sector in the fishery sector, economic growth which can directly improve the welfare of the fishing community. The purpose of this research is to be able to plan a strategy that must be implemented by the manager of the PPN Pengambengan to encourage the business development of service users in the PPN Pengambengan. The benefits obtained from this research are, to be able to improve the function of the PPN Pengambengan in serving the needs of coastal communities, fisher, the fishing industry, and other agencies so that they can directly develop the potential of resources around the port area both socially and economically. Data analysis in this research uses SWOT analysis with the stages of determining IFAS and EFAS, Matrix, SWOT Quadrants. The results of the study get an IFAS value of 0.34 (x), and an EFAS value of – 0.02 (y), where the value is in the Diversification Strategy position or using the ST strategy. The strategies offered for investment development in PPN Pengambengen are in the Diversification Strategy (ST) quadrant position, namely; transfer of fishing technology, controlling the loading and unloading process through improving K5 performance, special land for SPBN refueling, and expansion of road infrastructure for the fisheries industry to be adequate for the mobilization.